2013
DOI: 10.1104/pp.113.214536
|View full text |Cite
|
Sign up to set email alerts
|

Traffic of Human α-Mannosidase in Plant Cells Suggests the Presence of a New Endoplasmic Reticulum-to-Vacuole Pathway without Involving the Golgi Complex  

Abstract: The transport of secretory proteins from the endoplasmic reticulum to the vacuole requires sorting signals as well as specific transport mechanisms. This work is focused on the transport in transgenic tobacco (Nicotiana tabacum) plants of a human a-mannosidase, MAN2B1, which is a lysosomal enzyme involved in the turnover of N-linked glycoproteins and can be used in enzyme replacement therapy. Although ubiquitously expressed, a-mannosidases are targeted to lysosomes or vacuoles through different mechanisms acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Retention of Abs in the endoplasmic reticulum (ER) frequently results in increased yields (De Muynck et al ., ). Although the plant central vacuole is considered a hostile environment for foreign protein accumulation, it has been shown that some proteins, such as human alpha‐mannosidase (De Marchis et al ., ), human complement factor C5a, (Nausch et al ., ), collagen (Stein et al ., ) and human transglutaminase 2 (Marin Viegas et al ., ), accumulate in this organelle. In contrast, in carrot suspension cell cultures, secretory versions of human IgG1 and G4 have higher yields than ER and vacuolar variants (Shaaltiel et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Retention of Abs in the endoplasmic reticulum (ER) frequently results in increased yields (De Muynck et al ., ). Although the plant central vacuole is considered a hostile environment for foreign protein accumulation, it has been shown that some proteins, such as human alpha‐mannosidase (De Marchis et al ., ), human complement factor C5a, (Nausch et al ., ), collagen (Stein et al ., ) and human transglutaminase 2 (Marin Viegas et al ., ), accumulate in this organelle. In contrast, in carrot suspension cell cultures, secretory versions of human IgG1 and G4 have higher yields than ER and vacuolar variants (Shaaltiel et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Observing the behavior of a human lysosomal enzyme (α-mannosidase) expressed in plant cells, a new Golgi-independent vacuolar deliver of a soluble protein has been revealed. 8 In this paper it has been demonstrated that this glycoprotein is completely transported to the vacuole in a BFA-insensitive manner. Moreover, the processed α-mannosidase vacuolar fragments are not modified by Golgi enzymes, suggesting that this protein uses an alternative route the glycosylated proteins present in the Golgi.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, the processed α-mannosidase vacuolar fragments are not modified by Golgi enzymes, suggesting that this protein uses an alternative route the glycosylated proteins present in the Golgi. 8 In conclusion, even if the determinants that regulate this unconventional route are not yet well characterized, we think that its importance for the regulation of cell functionality in eukaryotes is becoming more and more evident.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Plants in particular seem to represent a promising system thanks to the cost-effective and easy production of lysosomal proteins with already successful attempts of expressing human hydrolases such as mannosidases and glucocerebrosidase [61,62]. Most importantly, plant-produced (carrot) recombinant human glucocerebrosidase has been shown to naturally possess terminal mannose residues, a step which has to be additionally performed in vitro for Chinese hamster ovary (CHO)-derived glucocerebrosidase [63].…”
Section: Resultsmentioning
confidence: 99%